Eksistensi Fungsi Dewan Perwakilan Daerah Sebagai Lembaga Perwakilan Daerah Dalam Sistem Bikameral - Nyoman Nidia Sari Hayati (Rechtsvinding, 2023)
DPD is a representative body that was born on the third amendment of the 1945 Constitution which is the representation of the people of the area which is a representative second chamber after the House of Representatives. Interest DPD formed to represent local people's voice with various laws in favor of the local community. However, the regulations and the Act does not provide the appropriate authority of the DPD is different from the authority given to the House of Representatives. This differs from the various countries of the world are on a strong power authority in the legislative for DPD called to the Upper House or Senate. This research was conducted with the comparative method is to provide a comparison authority of the DPD in various countries of the world and the historical approach to determine the origin and development of DPD and bicameral system.